Electron transfer within β-diketiminato nickel bromide and cobaltocene redox couples activating CO2. Issue 7 (4th January 2021) - Zimmermann, Philipp; Kilpatrick, Alexander F. R.; Ar, Deniz; Demeshko, Serhiy; Cula, Beatrice; Limberg, Christian
Abstract : Even though β-diketiminato nickel(ii ) bromide and cobaltocene have nearly identical redox potentials the corresponding electron transfer complex can be crystallised from the equilibrium and activates CO2 to form a mononuclear nickel(ii ) carbonate. Abstract : Reduction of β-diketiminato nickel(ii ) complexes (L t Bu Ni II ) to the corresponding nickel(i ) compounds does not require alkali metal compounds but can also be performed with the milder cobaltocenes. L t Bu NiBr and Cp2 Co have rather similar redox potentials, so that the equilibrium with the corresponding electron transfer compound [L t Bu Ni I Br][Cp2 Co III ] (ETC) clearly lies on the side of the starting materials. Still, the ETC portion can be used to activate CO2 yielding a mononuclear nickel(ii ) carbonate complex and ETC can be isolated almost quantitatively from the solutions through crystallisation. The more negative reduction potential of Cp*2 Co shifts the equilibrium formed with L t Bu NiBr strongly towards the ETC and accordingly the reaction of such solutions with CO2 is much faster.